Maize Yield Response to Zinc Sources and Effectiveness of Diagnostic Indicators. Issue 2 (19th January 2016) - Ruffo, Matías; Olson, Ron; Daverede, Inés
ABSTRACT: Maize yield is often limited by zinc (Zn) deficiency. The objectives of this study were to (i) evaluate maize yield response to Zn applied at four different rates, (ii) evaluate the yield response and agronomic efficiency of maize to the application of a complex fertilizer, MicroEssentials SZ (12N–40P–0K–10S–1Zn), compared to different rates of monoammonium phosphate (MAP) + ammonium sulfate (AS) + zinc sulfate (ZnSO4), and (iii) evaluate the association between tissue Zn concentration and soil-test Zn with the maize response to Zn fertilizer. Eleven experiments were carried out during the 2010, 2011, and 2012 growing seasons throughout eight states in the USA. Treatments consisted of four Zn rates of a physical blend of MAP + AS + ZnSO4 (0, 2.24, 4.48, 6.72, and 11.2 kg/ha Zn) and MicroEssentials SZ at a Zn rate of 2.24 kg/ha Zn. Nitrogen, phosphorus (P), and sulfur (S) rates were balanced across treatments (40 kg/ha P, 22 kg/ha S) and fertilizers were broadcast and incorporated immediately prior to planting. Treatment and location main effects were significant ( P  < 0.001) on corn yields, whereas the interaction treatment × location was not ( P  = 0.33). Maize responded positively to Zn fertilization; average yields across locations increased from 10, 540 kg ha −1 without Zn to 11, 530 kg ha −1 with 11.21 kg Zn ha −1 applied as a physical blend. The yield response and Zn agronomic efficiency of maize with the application of the complex fertilizer at a rate of 2.24 kg Zn ha −1 averaged 1004 kg ha −1 and 448 kg maize kg Zn −1, respectively, significantly higher ( P  < 0.1) than the yield response and Zn agronomic efficiency with the application of a physical blend with the same Zn rate, which averaged 293 kg ha −1 and 131 kg maize kg Zn −1, respectively. The Zn concentration in plant tissue of unfertilized plots varied greatly and was not related to the maize response to Zn fertilizer (r = 0.01; P  = 0.98). With respect to soil Zn, a negative but nonsignificant relationship was found between maize response to Zn fertilizer and soil-test Zn (r = −0.51; P  = 0.16).